The final phases of the Olival do Senhor dos Mártires necropolis (Alcácer do Sal, Portugal): the Roman Republican material - B. Gomes, Francisco; Alves, Catarina (SPAL - Revista de Prehistoria y Arqueología, 2017)
This contribution aims to present an ensemble of material of Roman Republican chronology exhumed in the necropolis of Olival do Senhor dos Mártires (Alcácer do Sal, Portugal). In order to assess the importance of this period in the overall phasing of the site, this ensemble – comprising black gloss pottery, amphorae, unguentaria and a terracotta figurine – is studied from a chronological, typological and functional point of view. The resulting framework of reference allows to propose that this area was probably continually used as a burial ground throughout the Republican period (mid-2nd to late 1st centuries BCE), thus putting the apparent hiatus between the Late Iron Age and the Imperial phases of the necropolis in perspective.